The efficiency of improvised humidor in preserving accurate dimensions of alginate impressions - Martinez, Renee Cerissa R.; Molina, Katherine S.; Galban, Angelita B. (Adviser).
The study was done to assess the efficiency of improvised humidor in preserving accurate dimensions of alginate impressions. Specifically, the researchers would like to determine the length of time and at what storage temperature an alginate impression in an improvised humidor demonstrates significant dimensional changes, which may affect the accuracy of fit of a removable partial denture framework on working casts. Using an experimental research design, the study compared the use of improvised humidor and immediate pouring of alginate impressions. There was one control group (immediately poured) and nine experimental groups (humidor stored at 1, 2, 3 hour intervals each stored under hot, room, and cold temperature) of alginate impressions. Three trials were done in each group. A total of 30 casts were obtained and the dimensions of these casts were measured and compared to baseline values. The casts were also evaluated on the ease of fit of the casted metal framework. Analysis of the data was done using one-way ANOVA [P<0.05] to compare each with the control group, followed by Post Hoc Tests using LSD [P<0.05] for multiple comparisons among groups. Post Hoc Test for multiple comparisons revealed that high temperature conditions under immediate pouring and 1 hour were statistically different from the conditions stored for 3 hours (P=0.037) for the rest seat preparation length of the first cylinder. Similarly, results showed that measurements made for the same dimension on the second cylinder stored under low temperature at all time intervals were statistically significant [P=0.001]. The experimental groups that exhibited clinical significance in terms of the fit of the metal framework on the cast included those stored in low temperature and for more than 2 hours. Thus, the improvised humidor is efficient in preserving accurate dimensions of alginate impressions when used for not more than 2 hours and when not placed in a cold environment.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dental impression materials; Dental impression technique